Description of three new species of Nymphistrini (Coleoptera: Histeridae: Haeteriinae) from Central America - Tishechkin, Alexey K.; Cárdenas, Alida Mercado (Zootaxa, 2012)
Three new species belonging to the tribe Nymphistrini of the obligate myrmeco- and termitophilous subfamily Haeteriinae (Coleoptera: Histeridae) are described from Central America: Nymphister rettenmeyeri sp. n. (Costa Rica and Panama), Trichoreninus carltoni sp. n. (Belize and Honduras) and T. neo sp. n. (Costa Rica and Panama). Identification keys for the Central American species of both genera are prepared. Available host records for N. rettenmeyeri confirm the symbiosis of the genus with Eciton army ants: the species has been found in colonies of E. burchelli (Westwood), E. hamatum (Fabricius) and E. mexicanum Roger. Host records are not available for the new species of Trichoreninus as all known specimens were collected by flight intercept traps.